Artisanal Businesses: Historical and Economic Context - Franci Daniela Alonso Aguilar; Tania Elena González Alvarado; Pablo Cabanelas Lorenzo (Mercados y Negocios)
The purpose of this paper is to examine the unique features of artisan enterprises in Ecuador and how cooperation programs and national peculiarities have influenced their development. Through descriptive and conceptual analysis, we can better understand how these organizations have evolved within the historical and economic context of rural regions in Ecuador. The primary findings suggest that poverty alleviation and control measures have significantly impacted the definition of artisan enterprises in Ecuador, which now closely resemble micro-enterprises. Development cooperation efforts in Ecuador have prioritized preserving artisanal production rather than replacing it with industrial production, promoting micro-enterprises growth as artisanal workshops.